A study of two FRBs with low polarization fractions localized with the MeerTRAP transient buffer system - Rajwade, Kaustubh M.; Driessen, L. N.; Barr, E. D.; Pastor-Marazuela, I.; Berezina, Marina; Jankowski, F.; Muller, A.; Kahinga, L.; Stappers, B. W.; Bezuidenhout, M. C.; Caleb, M.; Deller, A.; et al. (Monthly notices of the Royal Astronomical Society, 2024)
Localization of fast radio bursts (FRBs) to arcsecond and subarcsecond precision maximizes their potential as cosmological probes. To that end, FRB detection instruments are deploying triggered complex-voltage capture systems to localize FRBs, identify their host galaxy, and measure a redshift. Here, we report the discovery and localization of two FRBs (20220717A and 20220905A) that were captured by the transient buffer system deployed by the MeerTRAP instrument at the MeerKAT telescope in South Africa. We were able to localize the FRBs to precision of $\si
Online veröffentlicht: 5. Juli 2024, Korrektur und Schriftsatz: 30. Juli 2024
Gesehen am 06.10.2025